Outcome of pedicle screw fixation with transpedicular bone grafting in fracture of thoracolumbar vertebrae - Singh, Harpreet; Rampurwala, Aliasgar J.; Rudani, Tej S.; Gandhi, Malay P. (International Journal of Research in Orthopaedics, 2020)
Background: Posterior short segment instrumentation for thoracolumbar fracture is known for high implant failure rate because of the lack of anterior support. Anterior body augmentation by transpedicular bone grafting has been developed as an alternative to overcome this failure. In this study, we have evaluated the outcome of the cases of the unstable thoracolumbar spine injuries managed surgically with pedicle screws and transpedicular bone grafting. Methods: 20 patients were included in this study and were followed up for up to 6 months postoperatively. We assessed the outcome of each patient with Frankel scale and visual analog score (VAS) post-operatively clinically and radio logically by measuring Cobb’s angle and anterior vertebral body height post-operatively on follow-up at 6 weeks, 12 weeks, and 24 weeks. Results: We found that males had higher incidence with most common mode of injury was fall from height. D12 was single most involved vertebrae. The average Cobb’s angle during preoperative stage was 12 degrees and 22.05 degrees at 6th week and this was maintained till 24th week. The mean difference of anterior vertebral body height between pre-operative and 24th post-operative week was 7.15 mm. The mean VAS pre-operatively was 9.8 which changed to 0.75 at 24 weeks follow up. These were statistically highly significant. Conclusions: Our study established that Pedicle screw fixation with transpedicular bone grafting has a satisfactory result and can restore vertebral height, increase the stability of the injured vertebrae and leads to a significant improvement in the patient’s quality of life.